Discourse : a critical introduction - Blommaert, Jan (Key topics in sociolinguistics., 2005)
This engaging introduction offers a critical approach to discourse. Organised thematically, it begins by outlining the basic principles, and moves on to examine the methods and theory of CDA (critical discourse analysis). Topics covered include text and context, language and inequality, choice and determination, history and process, ideology and identity.